Implications of vascularized composite allotransplantation in plastic surgery on legal medicine - Haug, Valentin; Panayi, Adriana C.; Knoedler, Samuel; Foroutanjazi, Sina; Kauke-Navarro, Martin; Fischer, Sebastian; Hundeshagen, Gabriel; Diehm, Yannick; Kneser, Ulrich; Pomahac, Bohdan (Journal of Clinical Medicine, 2023)
Background: When a patient receives a transplant—be it classically an organ or bone marrow or, more recently, composite allotransplantations of the limb or face—it can result in artificial chimerism. Such chimerism raises considerations in forensic medicine, a field that relies on the collection and identification of biological samples from crime scenes. Beyond this chimerism, composite allotransplantations create further challenges. Methods: After screening the literature and press releases, we provide a brief history and summary of some of the technologies used in forensic identification, explaining their advantages and pitfalls in the light of transplantation and cautioning against misidentifying those who evade justice by taking advantage of such considerations. Results: With face transplantation, patients can receive the skin, hair, salivary glands, teeth, and oral and nasal mucosa of their donors, components which hold great importance in forensic science. Modern technologies such as computer-assisted facial recognition, although gradually becoming more accurate over time, also face new challenges in this post-transplantation era as facial recognition software can be misled by surgical alterations of the face or face transplantation. With limb transplantation, there is an impact on fingerprint identification. Conclusions: Both surgical transplantation techniques and forensic technologies have seen incomprehensibly great innovation in the past century. Given the growing rate of successful composite transplantation in the USA and worldwide, it is now important for law enforcement agents to be aware of the new possibility of having two sets of genetic material, hair, saliva, fingerprints, or even facial recognition data for the same individual.
Gesehen am 21.04.2023